Strategi Pembelajaran Anak Autisme Spectrum Disorder (ASD) di SD Negeri - Rohmah, Fiskiyatur; Fauzi Fadliansyah; Anna Maria Oktaviani (Arden Jaya Publisher, 2025)
This study aims to identify effective learning strategies for children with Autism Spectrum Disorder (ASD) at SDN Kelapa Dua 05. Children with ASD at this school face challenges in social interaction, concentration, and verbal communication. This research uses a qualitative approach with a second-grade student with ASD and their teacher as subjects. Data was collected through observation, interviews, and documentation. The findings show that a combination of several strategies proved to be effective. These strategies include: an individualized approach that tailors instructions to the child's abilities, the use of visual media such as flashcards to facilitate understanding, intensive guidance from the teacher and support from a deskmate, positive reinforcement through praise and appreciation, and active family involvement to continue the learning process at home. The consistent application of these strategies was proven to improve the academic and social skills of children with ASD.